The Impact of MSMEs, Population, Road Infrastructure, and Human Development Index on GRDP In Central Java - Eldeib, Manar Abdulsalam M; Maulana, Muhammad Rais Panji; Nasir, Muhammad Safar (JAMPE (Journal of Asset Management and Public Economy), 2025)
National economic development is an effort to improve people's welfare in order to fulfil their basic needs. This study analyses the effect of the number of Micro, Small, and Medium Enterprises (MSMEs), population, road infrastructure, and the Human Development Index (HDI) on Gross Regional Domestic Product (GRDP) in Central Java in 2018-2022 with the aim of knowing whether umkm, population, road infrastructure, and human development index affect GRDP. By using a descriptive quantitative approach using secondary data obtained from the Central Bureau of Statistics (BPS), this study uses statistical analysis to test the relationship. The results showed that although MSMEs and population did not have a significant effect on GRDP. This study makes a significant contribution to the Human Development Index (HDI) in Central Java so as to successfully build a human development index that is in line with the growth of GRDP, we can see from the results of the study which show that HDI has a positive effect on GRDP when HDI increases by 1 per cent, the value of GRDP will increase by Rp 2,185,483. Road infrastructure shows a significant positive effect. This finding suggests that investment in infrastructure and human development is an important driver of economic growth in the region.